Ecotourism, Foreign Tourist Perception, and National Parks: The Case in Northeast Langkawi - Boon Thong, Lee, (Malaysian Journal of Science, 2005)
Scientists from the University of Malaya have suggested that the northeast of Langkawi be declared as a national park by virtue of its great diversity. This paper argues that this suggestion is strengthened by adopting a dual approach of nature conservation and ecotourism. Some issues of ecotourism as it pertains to Northeast Langkawi are discussed. An analysis of tourist characteristics and perceptions shows a strong potential for ecotourism through the labelling of Northeast Langkawi as a national park